Defined extracellular matrix compositions support stiffness-insensitive cell spreading and adhesion signaling - Conway James R.W.; Isomursu Aleksi; Follain Gautier; Härmä Ville; Jou-Ollé Eva; Pasquier Nicolas; Välimäki Eetu P.O.; Rantala Juha K.; Ivaska Johanna (National Academy of Sciences, 2025)
Integrin-dependent adhesion to the extracellular matrix (ECM) mediates mechanosensing and signaling in response to altered microenvironmental conditions. In order to provide tissue- and organ-specific cues, the ECM is composed of many different proteins that temper the mechanical properties and provide the necessary structural diversity. Despite most human tissues being soft, the prevailing view from predominantly in vitro studies is that increased stiffness triggers effective cell spreading and activation of mechanosensitive signaling pathways. To address the functional coupling of ECM composition and matrix rigidity on compliant substrates, we developed a matrix spot array system to screen cell phenotypes against different ECM mixtures on defined substrate stiffnesses at high resolution. We applied this system to both cancer and normal cells and surprisingly identified ECM mixtures that support stiffness-insensitive cell spreading on soft substrates. Employing the motor-clutch model to simulate cell adhesion on biochemically distinct soft substrates, with varying numbers of available ECM–integrin–cytoskeleton (clutch) connections, we identified conditions in which spreading would be supported on soft matrices. Combining simulations and experiments, we show that cell spreading on soft is supported by increased clutch engagement on specific ECM mixtures and even augmented by the partial inhibition of actomyosin contractility. Thus, “stiff-like” spreading on soft is determined by a balance of a cell’s contractile and adhesive machinery. This provides a fundamental perspective for in vitro mechanobiology studies, identifying a mechanism through which cells spread, function, and signal effectively on soft substrates.